Prognostic Factors of Survival in a Randomized Phase III Trial (MPACT) of Weekly nab‐Paclitaxel Plus Gemcitabine Versus Gemcitabine Alone in Patients With Metastatic Pancreatic Cancer. (12th January 2015) - Tabernero, Josep; Chiorean, E. Gabriela; Infante, Jeffrey R.; Hingorani, Sunil R.; Ganju, Vinod; Weekes, Colin; Scheithauer, Werner; Ramanathan, Ramesh K.; Goldstein, David; Penenberg, Darryl N.; Romano, Alfredo; Ferrara, Stefano; et al.
Abstract : Background: nab ‐Paclitaxel in combination with gemcitabine has emerged as a new treatment option for patients with metastatic pancreatic cancer (MPC), based on superiority over gemcitabine demonstrated in the phase III MPACT trial. Previously, Karnofsky performance status (KPS) score and the presence of liver metastases were shown to be predictive of survival with nab‐ paclitaxel plus gemcitabine treatment. This analysis sought to further explore the relationship between clinical characteristics and survival in the MPACT trial and to identify potential predictors of overall survival and progression‐free survival in patients with MPC. Materials and Methods: Cox regression models adjusted for stratification factors and a stepwise multivariate analysis of prespecified baseline prognostic factors were performed. Results: Treatment effect was significantly associated with survival, with a similar magnitude of reduction in risk of death compared with the previously reported primary analysis. Treatment effect consistently favored nab ‐paclitaxel plus gemcitabine across the majority of the prespecified factors. In addition to KPS score and presence of liver metastases, age and number of metastatic sites were independent prognostic factors of overall and progression‐free survival. Baseline carbohydrate antigen 19‐9 was not found to be an independent prognostic factor of survival in this analysis. Conclusion: The results of this analysis confirm broad utility of nab ‐paclitaxel plus gemcitabine for the treatment of MPC. In addition, these findings suggest that KPS score, presence of liver metastases, age, and number of metastatic sites are important predictors of survival that may be useful when making treatment decisions and designing future clinical trials. Abstract : In the pivotal phase III MPACT trial, nab ‐paclitaxel plus gemcitabine demonstrated improved survival compared with gemcitabine alone. This analysis of the phase III study confirms the survival benefit of nab ‐paclitaxel plus gemcitabine across many prespecified prognostic factors and the broad utility of this regimen for patients with advanced pancreatic cancer.